If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2a + 4) = 9 Reorder the terms: 3(4 + 2a) = 9 (4 * 3 + 2a * 3) = 9 (12 + 6a) = 9 Solving 12 + 6a = 9 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6a = 9 + -12 Combine like terms: 12 + -12 = 0 0 + 6a = 9 + -12 6a = 9 + -12 Combine like terms: 9 + -12 = -3 6a = -3 Divide each side by '6'. a = -0.5 Simplifying a = -0.5
| x/3=0.3333333333333333333333333 | | -3/7y=10 | | 3x=0.9999999999 | | logt-3=log(17-4t) | | 42=x+.4x | | y=12-x^4-6x^3+11x^2 | | 5x-57=98 | | 4x+5y=1115 | | 2c+5=c-8 | | 6x+5y+6z-3x+2z=-7y | | 7=7-7 | | 13-4x=21-6x | | 8f+19=14 | | 0=3x^2+13x+4 | | (1+v)(5v+7)=0 | | -3(r+6)=-41 | | 3x-7-7x=5 | | f(x)=3cosx | | 5.3=9.3-0.5x | | 0=20t-4.9t^2 | | x/6=12/15 | | 2(2x-i)4x-6x= | | 4a+2b-6a+3a= | | 37.12=8g+3.84 | | (x-8)2/3=4 | | 5y+30=3x | | 3x-6/4=12 | | v^2-2v-5=0 | | 545/5 | | y/0.5=-6 | | 2x+(-3)=9 | | log(x+6)-log(6)=log(12) |